Advancing evidence-based decision making in LMICs: Focus of EdTech Hub’s work - Hennessy, Sara (EdTech Hub, 2021)
This blog sets out the Hub’s aims and approaches to identifying appropriate and effective uses of EdTech that can potentially raise learning outcomes in low- and middle-income countries (LMICs). Research shows that EdTech offers immense potential, but sustainable and positive change at scale has largely proved elusive in practice – particularly for marginalised learners where we focus our work.  To…
Keywords: _EdTechHub_Output

L'utilisation des preuves pour renforcer la formation pédagogique à travers les technologies à Madagascar - Koomar, Saalim; Moss Coflan, Caitlin; Rasolohéry, Hasiniavo (2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodoETH

Sierra Leone Series: Plan International and the importance of community support for distance teacher professional development programmes - McBurnie, Chris; Saidu, Arthur; Rincon Casado, Eusebio; Shergill, Maggie (EdTech Hub, 2021)
Keywords: _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:analysis:nopdf; _r:AddedByZotZen

Sierra Leone Series: the Pikin-to-Pikin Movement and its focus on child protection, education, nutrition and health - McBurnie, Chris; Swaray, Abdulai; Kamara, Bai (EdTech Hub, 2021)
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen

Sierra Leone series: Plan International and the importance of community support for distance teacher professional development programmes - Saidu, Arthur; Casado, Eusebio Rincon; Shergill, Maggie; McBurnie, Chris (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector.  In week four, we met with Arthur Saidu, Eusebio Rincon Casado and Maggie Shergill from…
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH

Using evidence to strengthen tech-supported teacher professional development in Madagascar - Koomar, Saalim; Moss Coflan, Caitlin; Rasolohéry, Hasiniavo (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _r:AddedByZotZen; _zenodoETH

Sierra Leone series: Freetown Teachers College and its multimodal approach to teacher professional development - McBurnie, Chris; Moriba, Sambo; Brainard, Prince (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector.  In week two, we connected with Dr Samba Moriba and Prince Brainard from Freetown Teachers…
Keywords: _DOILIVE; _EdTechHub_Output; _r:AddedByZotZen; _zenodoETH; dode_eth-src-eth

Mother Language Day 2021 - Haßler, Björn; Castillejo, Alice; Marzotto, Mia; El-Serafy, Yomna; Khalayleh, Abdullah; Koomar, Saalim; Langa, Ancha; Nyilinkindi, Jacques; Saadeddin, Zeina; Tegha, Ghislaine; Villavicencio Peralta, Xuzel Ana (2021)
To celebrate International Mother Language Day 2021, Björn spoke with Alice Castillejo and Mia Marzotto at Translators without Borders. We talked about the importance of mother tongue-based education and the need to support speakers of marginalised languages. Research around the world shows that educational outcomes are worse for students studying in a second language. The use of an unfamiliar language is linked to high dropout rates and low academic achievement. We also know that 40% of children worldwide are not educated in a language they speak at home. We need to put aside our assumptions about what languages people speak and understand. For example, Portuguese is only one of many languages spoken in Mozambique. To really understand the richness of different languages, we need to collect, share, and visualise the real picture. Having done that, we can then apply this information. Do children who speak a particular language drop out early? We can then develop multilingual educational tools for learners and teachers based on improved data about relevant languages. We can also track educational outcomes by primary language, to ensure no learner is left behind. We can use language data to take action on three levels: children, teachers, and systems. With children, we can identify which language groups didn’t register for school, dropped out early, or consistently underperform. We can then adjust our communication and programming to meet their needs, leaving no one behind. We can also take action to support teachers. With language data, we can also take action on a system level. If over 40% of children are educated in a language they don’t speak at home, we need to know how this affects their education. Much as we did for gender, if we don’t gather the data on inequality, we cannot begin to address it. Collective gathering and sharing of language data can allow us to understand how to increase learning outcomes for speakers of marginalised languages and provide the support they need and deserve.
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _r:AddedByZotZen; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Mother Language Day 2021: Improving data on mother-tongue languages for better learning outcomes - Haßler, Björn; Castillejo, Alice; Marzotto, Mia; El-Serafy, Yomna; Khalayleh, Abdullah; Koomar, Saalim; Langa, Ancha; Nyilinkindi, Jacques; Saadeddin, Zeina; Tegha, Ghislaine; Villavicencio Peralta, Xuzel Ana (EdTech Hub, 2021)
To celebrate International Mother Language Day 2021, EdTech Hub’s Björn Haßler spoke with Alice Castillejo and Mia Marzotto of Translators without Borders. They talked about the importance of mother tongue-based education and the need to support speakers of marginalised languages. This blog post captures their conversation. “How do we know that speakers of marginalised languages are left behind?” Alice: Research…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH